The Importance of the Split Blood Specimen in Postmortem Medicolegal Examinations: Methanol Intoxication - Ata Öztürk, Hatice Kübra; Güngör, Ahmet Yahya; Kurtuluş Dereli, Ayşe (The Bulletin of Legal Medicine, 2023)
The histopathological and toxicological analyzes of biological samples taken during autopsy are important in determining the cause of death in the suspicious deaths. However, no toxic substance can be detected in the analyzes performed in the postmortem period, especially in the treated cases. In this case, the stored split specimen at the first admission to the hospital can be examined. In this study, a 55-year-old male case who was found unconscious on the roadside and died during his treatment in the intensive care unit was presented. He had a history of drinking cologne. Although no toxic substance was found in postmortem samples, lethal dose of methanol and formic acid were detected in the analysis of the split blood specimen taken at the emergency unit admission. With this case, it is aimed to emphasize the importance of taking the split biological specimen in the first admission of forensic cases.